2022
DOI: 10.12928/telkomnika.v20i5.22440
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer diagnosis based on cytology pap smear image classification using fractional coefficient and machine learning classifiers

Abstract: Doctors and pathologists have long been concerned about determining the malignancy from cell images. This task is laborious, time-consuming and needs expertise. Due to this reason, automated systems assist pathologists in providing a second opinion to arrive at accurate decision based on cytology images. The classification of cytology images has always been a difficult challenge among the various image analysis approaches due to its extreme intricacy. The thrust for early diagnosis of cervical cancer has alway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Medical diagnosis has been upgraded by different tools and techniques like surgical analysis [ 31 ], EEG encoding [ 32 ], CT imaging [ 33 , 34 ], and surgical navigation [ 35 ]. The discrete wavelet and cosine transform were used by Kalbhor and colleagues in their research study [ 36 ] to extract characteristics. They used the fractional coefficient technique to effectively decrease the dimensionality of these characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…Medical diagnosis has been upgraded by different tools and techniques like surgical analysis [ 31 ], EEG encoding [ 32 ], CT imaging [ 33 , 34 ], and surgical navigation [ 35 ]. The discrete wavelet and cosine transform were used by Kalbhor and colleagues in their research study [ 36 ] to extract characteristics. They used the fractional coefficient technique to effectively decrease the dimensionality of these characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…However, all the CNN‐based models face challenges with limited receptive fields and lacks effective mechanisms for handling positional information within images 69 ; utilized an ensemble deep belief network to attain a higher accuracy of 97.20% and 99.00%, respectively, on Sipakmed and Herlev dataset, respectively. It is also observed that fine‐tuning the GoogleNet architecture 71 has resulted in higher accuracy compared to the proposed method, however, a more comprehensive and robust assessment of how well the model is likely to generalize to new and unseen data is not demonstrated.…”
Section: Resultsmentioning
confidence: 95%
“…In the second phase, machine learning classifiers and fuzzy min-max neural network is used for the classification process [27]. [26] sity Hospital Resize 256 × 256 transform curacy was obtained with DCT…”
Section: Proposed Methodologymentioning
confidence: 99%